The experience of family structure and family change on emerging adults: A focus on single parent households - Naidoo, Noelle (University of the Witwatersrand, Johannesburg, 2024)
This qualitative research study explores the complex dynamics between family structure, adverse childhood experiences (ACEs), and their impact on emerging adults in South Africa. Through semi-structured interviews, the study investigated the experiences and perspectives of eight emerging adults aged 18-25 as they retrospectively journeyed through changes within their family structure and the adverse childhood experiences encountered along the way. The study is grounded within the theoretical framework of the family stress model (FSM); however, Arnett’s (2000) theory of emerging adulthood is also significant to the study's conceptualisation. The study's findings highlighted several themes, namely, 1) the initial family structure and ACEs experienced; 2) the journey through family structure change; 3) the immediate impact following a change in family structure; and 4) the long-term impact following a change in family structure. The study draws attention to the nuances and complexities of nuclear, single-mother, cohabiting, extended, and stepfamilies while challenging the notion of “normal” and traditional nuclear families. Additionally, the study reveals the significance of changes in family structure and dynamics, such as divorce, separation, and emergence of new partners and stepfamilies, in influencing psychological, relational, educational, emotional, and behavioural outcomes in emerging adults. These outcomes ranged from immediate to long-term impacts, embracing adversities such as child abuse and neglect, witnessing intimate partner violence, financial difficulties, premature maturation, and trust issues. However, the study also revealed positive immediate and long-term effects highlighted throughout the findings, such as improved relationships, stability and security, empowerment, self- development, and optimistic self-reflections. The research study provides deeper insights into family structure changes and their consequences for emerging adults in South Africa while laying the foundation for future research.
A research report submitted in fulfillment of the requirements for the Master of Arts in Community-based Counselling Psychology, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Adverse childhood experiences; emerging adulthood; family stress model; family structure change; immediate impact; long-term impact; positive outcomes; South Africa; thematic analysis; SDG-5: Gender equality; SDG-1: No poverty